Web usage and perceptions of grade 11 students of De La Salle University Science and Technology Complex (DLSU-STC): The web as an information resource - Garcia, Justina P. (Animo Repository, 2012)
The web is a rich source of information brought about by modern technologies. This is widely used as source of educational information nowadays particularly in DLSU-STC, promoting the science and technology in the K-12 curriculum. The study sought to explore the web as an information resource in K-12 education focused on the web usage and perceptions of grade 11 students. Results of the study revealed that the students access the web often to do research and projects and the web is significantly used to complete their schoolwork. It was also known that the students perceive the web very helpful for their schoolwork and a reliable source of educational information. Thus, they expect that their reliance and use of the web will increase in the future. Significances and problems regarding the web usage and perceptions of the students were discussed and several recommendations were proposed.